2015
DOI: 10.1016/j.fsi.2014.10.033
|View full text |Cite
|
Sign up to set email alerts
|

N-hexanoyl-L-homoserine lactone-degrading Pseudomonas aeruginosa PsDAHP1 protects zebrafish against Vibrio parahaemolyticus infection

Abstract: a b s t r a c tFour strains of N-hexanoyl-L-homoserine lactone (AHL)-degrading Pseudomonas spp., named PsDAHP1, PsDAHP2, PsDAHP3, and PsDAHP4 were isolated and identified from the intestine of Fenneropenaeus indicus. PsDAHP1 showed the highest AHL-degrading activity among the four isolates. PsDAHP1 inhibited biofilm-forming exopolysaccharide and altered cell surface hydrophobicity of virulent green fluorescent protein (GFP)-tagged Vibrio parahaemolyticus DAHV2 (GFP-VpDAHV2). Oral administration of PsDAHP1 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In contrast with this, high levels of siderophores from the catechol group were identified in cell-free extracts of Pseudomonas PS-102 (Vijayan et al, 2006) able to inhibit the growth of several Vibrio and Aeromonas spp., suggesting investment in exploitation mechanisms. Similarly, CFCS of AHL-degrading P. aeruginosa strains, isolated from the intestine of F. indicus, was shown to inhibit more than 80% of biofilm formation by V. parahaemolyticus (Vinoj et al, 2015). Pseudomonas spp.…”
Section: Pseudomonasmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast with this, high levels of siderophores from the catechol group were identified in cell-free extracts of Pseudomonas PS-102 (Vijayan et al, 2006) able to inhibit the growth of several Vibrio and Aeromonas spp., suggesting investment in exploitation mechanisms. Similarly, CFCS of AHL-degrading P. aeruginosa strains, isolated from the intestine of F. indicus, was shown to inhibit more than 80% of biofilm formation by V. parahaemolyticus (Vinoj et al, 2015). Pseudomonas spp.…”
Section: Pseudomonasmentioning
confidence: 95%
“…Alternatively, some species can disrupt biofilm formation. For example, Pseudomonas aeruginosa PsDAHP1 (isolated from the Indian prawn Fenneropenaeus indicus ) has been found to antagonise the ability of Vibrio parahaemolyticus to form biofilms in zebrafish gills and intestine, resulting in a much looser architecture and possibly making them more susceptible to antimicrobials (Vinoj et al ., 2015).…”
Section: Competitive Exclusion Of Pathogenic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that probiotic fed fish had significantly higher resistance against A. hydrophila infection (Giri et al, 2012 ). Similarly, oral administration of P. aeruginosa PsDAHP1 inhibited biofilm formation and increased defense mechanisms which per se elevated zebrafish protection from V. parahaemolyticus DAHV2 infection (Vinoj et al, 2015 ).…”
Section: Probiotics and Bacterial Diseases In Fish (Table 1mentioning
confidence: 99%
“…The effect of AiiA-AgNPs on H.pylori biofilm formation was tested as mentioned previously [31]. Briefly, overnight grown culture of H. pylori ATCC 43504 was diluted to 1:100 in fresh BHI medium in the presence of AgNO 3 (2 µM), AiiA alone (120 U/ml), and different concentrations (1-5 µM) of AiiA-AgNPs in a 96-well microtiter plate and incubated for 48 h at 37°C.…”
Section: Biofilm and Ahl-lactonase Activity Bioassaymentioning
confidence: 99%